Exploring the Photocatalytic Potential of Lead-Free Cs2Ag x Na1–x BiCl6 Double Perovskites: Influence of Ag/Na Composition and Nanocrystalline Heterojunction Formation Induced by In Situ Water Interaction - do Nascimento Passini, Luan; Mattos, Bianca Oliveira; de Bona, Jéssica; da Silveira Lacerda, Luis Henrique; Rodrigues-Filho, Ubirajara Pereira; Ferreira-Neto, Elias Paiva [UNESP]; Manzani, Danilo (American Chemical Society (ACS), 2025)
Lead-free halide double perovskites (A2BIBIIIX6) have recently emerged as promising candidates in photocatalysis, demonstrating potential for applications such as CO2 photoreduction, H2 evolution, and organic pollutant degradation. However, the influence of monovalent metal cation composition, particularly Ag+ and Na+, on their photoactivity performance remains poorly understood, and their behavior in aqueous media has been insufficiently explored. In this study, we synthesized double perovskites, Cs2Ag x Na1–x BiCl6, with varying Ag/Na ratios and systematically evaluated their photocatalytic activity in both aqueous and ethanolic environments. Density Functional Theory (DFT) simulations were conducted to analyze their electronic structures and charge carrier stability. By correlating experimental characterization, theoretical calculations, and photocatalytic performance, we uncovered critical insights into the role of Ag+ and Na+ in tuning the photoactivity of these lead-free perovskites. Our results indicate that increasing the Ag+ content reduces the intrinsic photocatalytic activity of Bi-based double perovskites in ethanolic media, a trend attributed to changes in charge carrier stability, according to DFT. In contrast, the opposite effect was observed in aqueous media, where higher Ag+ concentrations enhanced photocatalytic performance. This behavior was linked to the complete structural conversion of the perovskite in water, leading to the in situ formation of a BiOCl/AgCl heterojunction with superior photocatalytic properties. These findings offer valuable insights into the interplay between composition, water stability, and photocatalytic efficiency, providing a foundation for the rational design of advanced photocatalysts derived from lead-free metal halide double perovskites.